2012
DOI: 10.1007/s00520-012-1448-1
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy-induced nausea and vomiting in clinical practice: impact on patients’ quality of life

Abstract: The results of the study confirm the detrimental effect of CINV on patients' QoL despite the use of antiemetic prophylaxis (5HT(3) receptor antagonist, steroids, and dopamine receptor antagonists). It is mandatory to intensify the detection of CINV in order to improve the management of these important, albeit frequent, side effects of cancer treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
94
0
12

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(114 citation statements)
references
References 29 publications
8
94
0
12
Order By: Relevance
“…Those authors observed that 40% to 45% of patients experienced CINV that significantly affected their quality of life, as estimated by a functional living index-emesis questionnaire, and that those who experienced significant nausea did so in 90% of chemotherapy cycles. 11 In another study of quality of life in a community hospital-based setting, approximately 33% of patients reported that CINV had a substantial impact on their daily lives. Both acute and delayed CINV affected quality of life, but only the presence of acute CINV influenced antiemetic treatment, suggesting that delayed effects are not being appropriately addressed.…”
Section: Discussionmentioning
confidence: 99%
“…Those authors observed that 40% to 45% of patients experienced CINV that significantly affected their quality of life, as estimated by a functional living index-emesis questionnaire, and that those who experienced significant nausea did so in 90% of chemotherapy cycles. 11 In another study of quality of life in a community hospital-based setting, approximately 33% of patients reported that CINV had a substantial impact on their daily lives. Both acute and delayed CINV affected quality of life, but only the presence of acute CINV influenced antiemetic treatment, suggesting that delayed effects are not being appropriately addressed.…”
Section: Discussionmentioning
confidence: 99%
“…This adverse event impairs patients' quality of life and exerts a negative influence on patient's desire to continue the chemotherapy (1,2).…”
mentioning
confidence: 99%
“…There are two symptoms that appear quite frequently so at this stage: the general feeling of wear without apparent cause and difficulties with memory. 8,9,13,[17][18][19][20] In this study 75,0% of patients were at this stage.…”
Section: Stress In Patients …mentioning
confidence: 85%
“…4,16,20 The nature of the symptoms, the majority of patients with stress had a greater amount of physical symptoms, followed by psychological symptoms. The prevailing stress resistance of the layer was followed by phase near exhaustion.…”
Section: Stress In Patients …mentioning
confidence: 99%